The Education for the Stone ": some glances on the artistic language in the youths and adults´ litteracy - Regina Aparecida Ribeiro Siqueira; Janaína Behling; Luiza Chu; Viviane Ramos da Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This paper presents some reflections of young and adult educators when situated, themselves, as subjects of their actions in a Painting Workshop. We analyzed an experience produced by PEJA - Projeto de Educação de Jovens e Adultos (Young and Adult Education Project) - Unesp/Assis. The educators of this project offered a Workshop entitled "Arts and Education: the arts as language in the education of youngsters and adults", destinated to educators of the City Board of Education Assis (SP) and to undergraduate students of the University. Each one of the participants was invited to make a picture, using various materials as the conventional brushes and paints, besides seeds, leaves, stones and a lot of sensibility to discuss pedagogical theory and practice. The Workshop took place in 2003, because of the V Education Journey of Unesp, with a total time of 8 hours.